Hypothalamic Obesity following Craniopharyngioma Surgery: Results of a Pilot Trial of Combined Diazoxide and Metformin Therapy. (1st March 2011) - Hamilton, Jill K.; Conwell, Louise S.; Syme, Catriona; Ahmet, Alexandra; Jeffery, Allison; Daneman, Denis
Abstract : Objective . To assess the effect of combined diazoxide-metformin therapy in obese adolescents treated for craniopharyngioma. Design . A prospective open-label 6-month pilot treatment trial in 9 obese subjects with craniopharyngioma. Diazoxide (2 mg/kg divided b.i.d., maximum 200 mg/day) and metformin (1000 mg b.i.d.). Whole body insulin sensitivity index (WBISI) and area-under-the-curve insulin (AUCins ) were calculated. Results . Seven subjects completed: 4M/3F, mean ± SD age15.4 ± 2.9 years, weight99.7 ± 26.3  kg, BMI35.5 ± 5.6  kg/m 2, and BMI SDS2.3 ± 0.3 . Two were withdrawn due to vomiting and peripheral edema. Of participants completing the study, the mean ± SD weight gain, BMI, and BMI SDS during the 6 months were reduced compared to the 6 months prestudy (+ 1.2 ± 5.9 versus+ 9.5 ± 2.7  kg, P = .004 ;− 0.3 ± 2.3 versus+ 2.2 ± 1.5  kg/m 2, P = .04 ;− 0.04 ± 0.15 versus+ 0.11 ± 0.08, P = .021, resp.). AUCins correlated with weight loss (r = 0.82, P = .02 ) and BMI decrease (r = 0.96, P = .009 ). Conclusion . Combined diazoxide-metformin therapy was associated with reduced weight gain in patients with hypothalamic obesity. AUCins at study commencement predicted effectiveness of the treatment.